2015
DOI: 10.1186/s40168-015-0071-z
|View full text |Cite
|
Sign up to set email alerts
|

Maternal fucosyltransferase 2 status affects the gut bifidobacterial communities of breastfed infants

Abstract: BackgroundIndividuals with inactive alleles of the fucosyltransferase 2 gene (FUT2; termed the ‘secretor’ gene) are common in many populations. Some members of the genus Bifidobacterium, common infant gut commensals, are known to consume 2′-fucosylated glycans found in the breast milk of secretor mothers. We investigated the effects of maternal secretor status on the developing infant microbiota with a special emphasis on bifidobacterial species abundance.ResultsOn average, bifidobacteria were established earl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
313
3
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 355 publications
(337 citation statements)
references
References 102 publications
(111 reference statements)
18
313
3
3
Order By: Relevance
“…Therefore, differences in selectivity for certain HMOs likely contribute to variance among species of Bifidobacterium and Bacteroides isolated from feces of BF infants. Lewis et al 76 showed that bifidobacterial colonization was delayed in infants consuming HM from non-secretor mothers that is devoid of a particular type of HMO, 2-fucosyllactose (2FL), further supporting this theory regarding a possible origin for variations in Bifidobacterium observed among BF infants. This further leads to the question of how these HMOs interact with commensal bacteria residing in HM, and in turn, how this complex network of HM components functions in the n€ aive infant GI tract.…”
Section: Human Milk Oligosaccharidesmentioning
confidence: 95%
“…Therefore, differences in selectivity for certain HMOs likely contribute to variance among species of Bifidobacterium and Bacteroides isolated from feces of BF infants. Lewis et al 76 showed that bifidobacterial colonization was delayed in infants consuming HM from non-secretor mothers that is devoid of a particular type of HMO, 2-fucosyllactose (2FL), further supporting this theory regarding a possible origin for variations in Bifidobacterium observed among BF infants. This further leads to the question of how these HMOs interact with commensal bacteria residing in HM, and in turn, how this complex network of HM components functions in the n€ aive infant GI tract.…”
Section: Human Milk Oligosaccharidesmentioning
confidence: 95%
“…This significantly impacts the quantity and quality of oligosaccharides found in breast milk [100], potentially modifying any direct or indirect effects of breastfeeding on oral vaccine efficacy. Ultimately, the HBGA status of a mother-infant pair may play a role in shaping infant microbiota composition [101,102], mucosal immune development and pathogen receptor expression (in breast milk, mucus and on intestinal epithelial cells), thereby influencing both pathogen susceptibility and oral vaccine outcomes. However, further work is required to disentangle these pathways.…”
Section: Histo Blood Group Antigensmentioning
confidence: 99%
“…The MRM chromatograms (Figure 2) illustrated the variations between secretor (gray) and nonsecretor (black) milk from the US lactation study. The mothers were genotyped using a saliva test (39). As shown, milk from secretor mothers contained much higher concentrations of a(1,2)-fucosylated HMOs such as 2#FL, LNFP I, lacto-difucotetraose (LDFT), trifucosyllacto-Nhexaose, and tetrafucosyl-iso-lacto-N-octaose than did milk from nonsecretors.…”
Section: Quantitation Of Individual Hmo Compoundsmentioning
confidence: 99%